2022
DOI: 10.3389/fendo.2022.927859
|View full text |Cite
|
Sign up to set email alerts
|

Use of GLP-1 Receptor Agonists and Occurrence of Thyroid Disorders: a Meta-Analysis of Randomized Controlled Trials

Abstract: The association between glucagon-like peptide-1 (GLP-1) receptor agonists and the risk of various kinds of thyroid disorders remains uncertain. We aimed to evaluate the relationship between the use of GLP-1 receptor agonists and the occurrence of 6 kinds of thyroid disorders. We searched PubMed (MEDLINE), EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL) and Web of Science from database inception to 31 October 2021 to identify eligible randomized controlled trials (RCTs). We performed meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 77 publications
(49 reference statements)
1
25
0
Order By: Relevance
“…These disease states are often comorbid, and one affects the disease progression of the other 28 . However, the potential molecular mechanisms responsible for thyroid effects of GLP-1 RAs are insufficiently characterized and may include multiple pathways such as phosphoinositol-3 kinase/AKT serine/threonine kinase, mitogen-activated protein kinase/extracellular signal-regulated kinase pathways, expression GLP-1 receptors by C-cells, and GLP-1 association with triiodothyronine levels 21,29 . Thyroid hormone plays a pivotal role in nearly every aspect of lipid metabolism 30,31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These disease states are often comorbid, and one affects the disease progression of the other 28 . However, the potential molecular mechanisms responsible for thyroid effects of GLP-1 RAs are insufficiently characterized and may include multiple pathways such as phosphoinositol-3 kinase/AKT serine/threonine kinase, mitogen-activated protein kinase/extracellular signal-regulated kinase pathways, expression GLP-1 receptors by C-cells, and GLP-1 association with triiodothyronine levels 21,29 . Thyroid hormone plays a pivotal role in nearly every aspect of lipid metabolism 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…The thyroid cancer association in humans has been studied and observed as well in retrospective studies [18][19][20] . However, there is conflicting evidence from a meta-analysis of human randomized controlled trials which refutes this association 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that GLP-1 receptor agonists may cause thyroid C-cell adenomas and C-cell carcinomas in rodents ( 26 , 27 ), and thus GLP-1 receptor agonists are contraindicated in those with a history of medullary thyroid cancer. However, the LEADER trial ( 28 ) in T2DM patients and a meta-analysis ( 29 ) excluded a major increase in the risk of total malignant neoplasms (including pancreatic and thyroid neoplasms) with liraglutide treatment. In the present study, we further evaluated the relationship between thyroid function and GSEA.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In a meta-analysis of 11 trials, there was no increase in the risk of thyroid disorders in participants treated with semaglutide relative to placebo (RR = 0.75; 95% CI = 0.35, 1.57). 65 However, these events are rare, and people at individual or familial risk for MTC and MEN 2 and those with high baseline calcitonin were excluded from the STEP trials. In addition, most studies have been of relatively short duration.…”
Section: Candidates For Semaglutidementioning
confidence: 99%